The Physiological Responses of Water Hyacinth (Eichhornia crassipes (Mart). Solms) and Water Lettuce (Pistia stratiotes L.) as Trivalent Chromium Bioaccumulator - Rizka Purnamawati; T Taufikurahman; Andira Rahmawati; Chalvin Rura Putra; Din Dzakamala Fafi Rahmatilah; Findy Ashgi (School of Life Sciences and Technology, Institut Teknologi Bandung, 2020)
Chromium is one of the heavy metals used in industrial fields, i.e., metallurgical industry, chemical industry, heat-retardant, and leather tanning industry. Untreated wastewater from these industries can pollute rivers and threaten the aquatic ecosystem. Some aquatic plants such as water hyacinth (Eichhornia crassipes) and water lettuce (Pistia stratiotes) have been known as metal hyperaccumulators and can be used as phytoremediator for polluted water. This study aims to determine the physiological and morphological responses of water hyacinth and water lettuce plants treated by different concentrations of trivalent chromium and to study which plant is effective for trivalent chromium removal. The experiment was conducted for 2 week at screen house. After two weeks, the plants were harvested and the weight was measured. The samples were separated into shoot and root and were analyzed for Cr content, chlorophyll, proline and CAT enzyme activity. The results of this study indicated that the levels of water hyacinth chromium in roots and leaves are lower (863.988 mg/Kg, 899.126 mg/Kg, 685.877 mg/Kg for treatment 40 ppm, 80 ppm, and 120 ppm respectively) than the levels of chromium in water lettuce (1584.264 mg/Kg, 1660 mg/Kg, 1413 mg/Kg for treatment 40 ppm, 80 ppm, and 120 ppm respectively). Physiological parameter, i.e., chlorophyll and proline levels in water hyacinth and water lettuce from all concentration treatment did not differ significantly (P> 0.05). The activity of the catalase enzyme in water hyacinth and water lettuce decreased with increasing chromium levels. The highest catalase enzyme activity was observed in control treatment of water lettuce (1.61 unit/mg) and 40 ppm treatment of water hyacinth (1.006 unit/mg). The highest biomass dry weight of both plants was found in plants with control treatment (15.38 gr and 8.48 gr for water hyacinth and water lettuce respectively). Therefore, we concluded that water lettuce is better for trivalent chromium removal than water hyacinth.